Application of Dynamic Visual Communication Design in Digital Media (Journal of Global Humanities and Social Sciences, 2024)
With the rapid development of digital media technology, dynamic visual communication design plays an increasingly important role in modern communication. This paper discusses the basic concept of dynamic visual communication design and its application in advertising, multimedia, film and television, and digital product design, and analyses its importance in enhancing user interaction, information transfer efficiency and visual experience. Then it puts forward the development strategies of diversified interactive experience design, personalised and customised design, multi-sensory fusion design and cross-platform seamless integration design, aiming to provide reference for the further development of dynamic visual communication design in the future. With the advancement of technology, dynamic visual communication design will play a wider role in digital media, promote the development of multi-sensory integration and personalised experience, and bring more immersive interactive experience to users.